2021
DOI: 10.3390/rs14010176
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Forest Aboveground Biomass Using Gaofen-1 Images, Sentinel-1 Images, and Machine Learning Algorithms: A Case Study of the Dabie Mountain Region, China

Abstract: Quantitatively mapping forest aboveground biomass (AGB) is of great significance for the study of terrestrial carbon storage and global carbon cycles, and remote sensing-based data are a valuable source of estimating forest AGB. In this study, we evaluated the potential of machine learning algorithms (MLAs) by integrating Gaofen-1 (GF1) images, Sentinel-1 (S1) images, and topographic data for AGB estimation in the Dabie Mountain region, China. Variables extracted from GF1 and S1 images and digital elevation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 65 publications
(108 reference statements)
3
23
0
Order By: Relevance
“…Meanwhile, Wang et al demonstrated the potential of the simultaneous use of HJ-1B and RadarSat-2 data to estimate AGB in the desert grasslands of Ningxia, China (R 2 = 0.71, RMSE = 14.20 kg/hm 2 ), which outperformed the AGB estimation based on the NDVI index of HJ-1B (R 2 = 0.27, RMSE = 20.58 kg/hm 2 ) [69]. Therefore, we argue that combining the strengths of optical remote sensing data and radar data enables better quantitative estimation of AGB of UGS, an inference that agrees with several studies [70][71][72][73].…”
Section: Discussionsupporting
confidence: 88%
“…Meanwhile, Wang et al demonstrated the potential of the simultaneous use of HJ-1B and RadarSat-2 data to estimate AGB in the desert grasslands of Ningxia, China (R 2 = 0.71, RMSE = 14.20 kg/hm 2 ), which outperformed the AGB estimation based on the NDVI index of HJ-1B (R 2 = 0.27, RMSE = 20.58 kg/hm 2 ) [69]. Therefore, we argue that combining the strengths of optical remote sensing data and radar data enables better quantitative estimation of AGB of UGS, an inference that agrees with several studies [70][71][72][73].…”
Section: Discussionsupporting
confidence: 88%
“…One of the main challenges in AGB estimation methods and procedures is the ability to establish a reliable estimation protocol in new and complex ecosystems. Recent studies showed the strength and capabilities of various machine learning approaches to estimating AGB [69,16,70,18]. We suggest improving the current understanding and ML methods and using it in complex forests with a more generalized approach.…”
Section: Machine Learning Capabilities In Various Forest Ecosystemsmentioning
confidence: 94%
“…BP is a multilayer feed-forward network based on the error back propagation method, which is particularly good at handling non-linear and uncertain problems. The BP consists of input layers, implicit layers and output layers, and contains two stages: forward propagation and back propagation of the error [52]. The error is back-propagated through the implicit layer to the output layer, and apportioned to all units in each layer, until the error is eventually decreased to an acceptable level after continual training [53].…”
Section: Traditional Regression Methodsmentioning
confidence: 99%